Effects of storage time and temperature on the infectivity and effectiveness of Frankia entrapped in polyacrylamide gel - Sayed, W F; Wheeler, C T; el-Sharouny, H M; Mohawad, S M; Abdel-Karim, M M (Folia microbiologica, 2002)
Four Frankia-Casuarina endosymbiont strains were tested for their infectivity and effectiveness on C. equisetifolia plants after 1 d, 3 and 6 months of Frankia storage at 7, 28 and 40 degrees C as liquid-cultures and polyacrylamide gel (PAG)-immobilized inocula. At lower temperature the number of nodules was the same or higher than control for liquid inocula except after 6 months of storage. For the PAG-entrapped Frankia lower numbers of nodules were recorded due to the use of high Frankia titers. In general, the results showed comparable plant dry mass, total nitrogen, root to shoot and nodules to plant ratios at lower temperature treatments. Increasing time and temperature was accompanied with reduced infectivity and effectiveness on inoculated plants. No nodulation was scored on plants inoculated with liquid and PAG-entrapped inocula stored at 40 degrees C for 6 months; subsequently, plant growth was inhibited. The variations in results obtained for different strains and treatments lead to variations in plant nitrogen-fixing ability. The use of PAG as a carrier for different Frankia strains is suggested; the recommended storage temperature for PAG-immobilized Frankia in 7-28 degrees C for up to 3 months.
Keywords: akrylové pryskyřice; kořeny rostlin; rostliny; Acrylic Resins; Culture Media; Microbiological Techniques; Symbiosis; mikrobiologické techniky; Plant Roots; Temperature; symbióza; Frankia; Plants; teplota; kultivační média